2011
DOI: 10.1007/s10682-011-9506-6
|View full text |Cite
|
Sign up to set email alerts
|

Heat tolerance, temperature acclimation, acute oxidative damage and canalization of haemoglobin expression in Daphnia

Abstract: Daphnia is a widespread freshwater zooplankton species, which is both a classic and emerging new model for research in ecological physiology, ecotoxicology and evolutionary biology of adaptation to novel environments. Heat tolerance in Daphnia is known to depend both upon evolutionary history of a genotype and on individuals' acclimation to elevated temperature and to correlate with the level of haemoglobin expression. We demonstrate the existence of north-south gradient of heat tolerance in North American D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 70 publications
10
52
1
Order By: Relevance
“…period over which the region where the lake was situated experienced a temperature increase of 1.15°C. Together with these previous findings, our results provide solid proof that Daphnia can evolutionary track environmental warming, not only along large-scale temperature gradients (Geerts et al, 2014;Williams et al, 2011;Yampolsky et al, 2014) or through time (Geerts et al, 2015), but also along smaller scale spatial disturbance gradients such as the urbanization gradients studied here. Together with these previous findings, our results provide solid proof that Daphnia can evolutionary track environmental warming, not only along large-scale temperature gradients (Geerts et al, 2014;Williams et al, 2011;Yampolsky et al, 2014) or through time (Geerts et al, 2015), but also along smaller scale spatial disturbance gradients such as the urbanization gradients studied here.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…period over which the region where the lake was situated experienced a temperature increase of 1.15°C. Together with these previous findings, our results provide solid proof that Daphnia can evolutionary track environmental warming, not only along large-scale temperature gradients (Geerts et al, 2014;Williams et al, 2011;Yampolsky et al, 2014) or through time (Geerts et al, 2015), but also along smaller scale spatial disturbance gradients such as the urbanization gradients studied here. Together with these previous findings, our results provide solid proof that Daphnia can evolutionary track environmental warming, not only along large-scale temperature gradients (Geerts et al, 2014;Williams et al, 2011;Yampolsky et al, 2014) or through time (Geerts et al, 2015), but also along smaller scale spatial disturbance gradients such as the urbanization gradients studied here.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, we tested whether populations of the water flea Daphnia magna have adapted to urban heat island effects through an increased thermal tolerance compared to rural populations. To explore the role of two possible underlying processes driving thermal tolerance, we also quantified body size and haemoglobin (Hgb) concentrations in all genotype x environment combinations (Klockmann, Günter, & Fischer, 2017;Williams, Dick, & Yampolsky, 2011). It has recently been shown that populations of this species can and have evolved in their thermal tolerance in response to climate change (Geerts et al, 2015).…”
mentioning
confidence: 99%
“…Heugens et al (2003) indicated that an increase in temperature increased the Cd k u (i.e., the Cd k u at 26 and 20 8C were similar, but the Cd k u at 20 8C was higher than at 10 8C). In the present study, the organisms were pre-acclimated to the temperature treatments, which in ectothermic organisms is essential to allow physiological adjustment to the environmental temperature (Williams et al 2012). However, in Heugens et al (2003), a single clone was tested, the test organisms were not pre-acclimated to the temperature treatments, and a different metal (Cd) was studied.…”
Section: Effect Of Temperature On Ni Uptake and Elimination In Daphnimentioning
confidence: 99%
“…For Daphnia, an ectothermic organism and a well-known ecotoxicological model organism, only a single study is available concerning the effect of temperature on metal toxicokinetics. However, Heugens et al (2003) did not acclimate the test organisms to the different temperature treatments prior to metal exposure, whereas an acclimation period is necessary to allow the test organisms to physiologically adjust to the environmental temperature (Williams et al 2012). However, Heugens et al (2003) did not acclimate the test organisms to the different temperature treatments prior to metal exposure, whereas an acclimation period is necessary to allow the test organisms to physiologically adjust to the environmental temperature (Williams et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, studies of geographical variation in Daphnia have provided evidence for both phenotypic plasticity and genetic population differentiation [22][23][24][25]. However, despite ample genetic variation among genotypes and populations, no evidence for local adaptation was found in this system.…”
Section: Introductionmentioning
confidence: 99%